Streptococcus canis Are a Single Population Infecting Multiple Animal Hosts Despite the Diversity of the Universally Present M-Like Protein SCM - Pinho, Marcos D.; Foster, Geoffrey; Pomba, Constança; Machado, Miguel P.; Baily, Johanna L.; Kuiken, Thijs; Melo-Cristino, José; Ramirez, Mário; , The Portuguese Group for the Study of Streptococcal Infections; Vaz, Teresa; Gião, Marília; Ferreira, Rui; et al. (Frontiers in Microbiology, 2019)
Streptococcus canis is an animal pathogen which occasionally causes infections in humans. The S. canis M-like protein (SCM) encoded by the scm gene, is its best characterized virulence factor but previous studies suggested it could be absent in a substantial fraction of isolates. We studied the distribution and variability of the scm gene in 188 S. canis isolates recovered from companion animals (n = 152), wild animal species (n = 20), and humans (n =14). Multilocus sequence typing, including the first characterization of wildlife isolates, showed that the same lineages are present in all animal hosts, raising the possibility of extensive circulation between species. Whole-genome analysis revealed that emm-like genes found previously in S. canis correspond to divergent scm genes, indicating that what was previously believed to correspond to two genes is in fact the same scm locus. We designed primers allowing for the first time the successful amplification of the scm gene in all isolates. Analysis of the scm sequences identified 12 distinct types, which could be divided into two clusters: group I (76%, n = 142) and group II (24%, n = 46) sharing little sequence similarity. The predicted group I SCM showed extensive similarity with each other outside of the N-terminal hypervariable region and a conserved IgG binding domain. This domain was absent from group II SCM variants found in isolates previously thought to lack the scm gene, which also showed greater amino acid variability. Further studies are necessary to elucidate the possible host interacting partners of the group II SCM variants and their role in virulence.